Long-Term Safety and Efficacy in Continued Access Left Atrial Appendage Closure Registries - Holmes, David R.; Reddy, Vivek Y.; Gordon, Nicole T.; Delurgio, David; Doshi, Shephal K.; Desai, Amish J.; Stone, James E.; Kar, Saibal (Journal of the American College of Cardiology, 2019)
Long-term data on the safety and efficacy of left atrial appendage closure (LAAC) for stroke prevention in patients with nonvalvular atrial fibrillation remain limited. The purpose of this study was to evaluate 4.5- to 5-year data in 2 U.S. Food and Drug Association LAAC mandated registries (CAP [Continued Access to PROTECT-AF] and CAP2 [Continued Access to PREVAIL]) for safety and efficacy. Two registries of patients implanted with LAAC devices provide the largest source of follow-up data. Both accompanied their respective randomized clinical trials, PROTECT-AF (Watchman Left Atrial Appendage System for Embolic PROTECTion in Patients With Atrial Fibrillation) and PREVAIL (Prospective Randomized Evaluation of the WATCHMAN LAA Closure Device In Patients with Atrial Fibrillation versus Long Term Warfarin Therapy), which used the same endpoints (primary efficacy of composite of stroke, systemic embolism, cardiovascular/unexplained death, and safety). CAP included 566 patients with an average follow-up of 50.1 months (2,293 patient-years), and CAP2 included 578 patients with an average follow-up of 50.3 months (2,227 patient-years). CAP2 patients were significantly older and had higher CHA2DS2-VASc (congestive heart failure, hypertension, age ≥75 years, diabetes mellitus, stroke/transient ischemic attack, vascular disease, age 65 to 74 years, sex category) scores (4.51 vs. 3.88; p < 0.001). Procedural success was similar in both (94%). The primary composite endpoint occurred at a rate of 3.05 per 100 patient-years in CAP and 4.80 per 100 patient-years in CAP2; events contributing to this endpoint were most commonly cardiovascular/unexplained death (1.69 per 100 patient-years for CAP and 2.92 per 100 patient-years for CAP2). Hemorrhagic stroke was significantly less than ischemic stroke (0.17 per 100 patient-years in CAP and 0.09 per 100 patient-years in CAP2), and total stroke rates were significantly less than predicted by CHA2DS2-VASc score (78% reduction with CAP, 69% reduction with CAP2). These registries, which contain the longest and largest follow-up data of patients with the Watchman device, support LAAC as a safe and effective therapy for long-term anticoagulation in patients with nonvalvular atrial fibrillation, and document the lowest rate of hemorrhagic stroke identified in this population. [Display omitted]